Mutational Analysis of the Phosphate-Binding Loop of Rhizobium meliloti DctD, a ς(54)-Dependent Activator - Gao, Yan (American Society for Microbiology, 1998)
The phosphate-binding loop of ς(54)-dependent activators is thought to participate in ATP binding and/or hydrolysis. Alanine substitutions at positions 3, 4, 6, 7, and 8 of this motif in Rhizobium meliloti DctD disrupted transcriptional activation and ATP hydrolysis. Interestingly, substitution of alanine at position 7 also affected DNA binding.